THE LEGAL REGULATION OF ELECTRONIC MONEY (COMPARATIVE STUDY) - Swidan, Hashem (جامعة النجاح الوطنية, 2022)
Electronic money is one of the secrets of the technical revolution in the field of telecommunications which emerged as a result of the growing trend in e-commerce, interpersonal transactions have become electronic which has created many means of payment that are commensurate with electronic commerce, These include electronic money, which is one of the means to be used by individuals to fulfil their obligations and transfer funds through it. The study dealt with the legal regulation of electronic money by reviewing its legal nature and nature, adapting the legal relationships that arise in relation to its transaction and the civil liability resulting from the transaction of electronic money, as well as the methods of proof of payment made through it As a result of the divergence of views on the legal nature of electronic money and the adoption of multiple opinions in jurisprudence there are those who consider it to be one of the existing forms of money and another aspect of the doctrine considers it to be a new form of money added to the existing forms. E-money ", which had to be reviewed and discussed in detail. The researcher concluded that electronic money could not be regarded as a new form of money but rather as an innovative means of electronic fulfilment that had been created by the technical development in the field of communications. The study came in three chapters, the first of which dealt with the nature, characteristics and possible forms of electronic money, and a distinction was made between electronic money and similar payment methods based on electronic means. In chapter II, the researcher presented the legal nature of electronic money and adapted the relationships arising therefrom. The researcher discussed the views expressed in the interpretation of the nature of legal money and the relationships arising therefrom. The opinion that the researcher deems most appropriate in determining the legal nature of electronic money and the legal relations arising therefrom was reached. Then, in the last chapter, the researcher moved to look for civil liability of electronic money and how to prove the payment process. Civil liability arising from the illicit use of electronic money, Addressing the contractual and default liability that may arise with respect to parties engaged in electronic money and then how to prove the payment of electronic money, and the authenticity of writing and electronic forecasting in proof of payment by electronic money. The study concluded with a number of findings and recommendations reached through the study.
THE LEGAL REGULATION OF ELECTRONIC MONEY (COMPARATIVE STUDY)
Electronic money is one of the secrets of the technical revolution in the field of telecommunications which emerged as a result of the growing trend in e-commerce, interpersonal transactions have become electronic which has created many means of payment that are commensurate with electronic commerce, These include electronic money, which is one of the means to be used by individuals to fulfil their obligations and transfer funds through it. The study dealt with the legal regulation of electronic money by reviewing its legal nature and nature, adapting the legal relationships that arise in relation to its transaction and the civil liability resulting from the transaction of electronic money, as well as the methods of proof of payment made through it As a result of the divergence of views on the legal nature of electronic money and the adoption of multiple opinions in jurisprudence there are those who consider it to be one of the existing forms of money and another aspect of the doctrine considers it to be a new form of money added to the existing forms. E-money ", which had to be reviewed and discussed in detail. The researcher concluded that electronic money could not be regarded as a new form of money but rather as an innovative means of electronic fulfilment that had been created by the technical development in the field of communications. The study came in three chapters, the first of which dealt with the nature, characteristics and possible forms of electronic money, and a distinction was made between electronic money and similar payment methods based on electronic means. In chapter II, the researcher presented the legal nature of electronic money and adapted the relationships arising therefrom. The researcher discussed the views expressed in the interpretation of the nature of legal money and the relationships arising therefrom. The opinion that the researcher deems most appropriate in determining the legal nature of electronic money and the legal relations arising therefrom was reached. Then, in the last chapter, the researcher moved to look for civil liability of electronic money and how to prove the payment process. Civil liability arising from the illicit use of electronic money, Addressing the contractual and default liability that may arise with respect to parties engaged in electronic money and then how to prove the payment of electronic money, and the authenticity of writing and electronic forecasting in proof of payment by electronic money. The study concluded with a number of findings and recommendations reached through the study.
Keywords: money, e-money, e-payment, e-commerce, e-proof.